Immunomodulatory Plants: A Phytopharmacological Review - sagrawat, Hemant; Khan, Md. Yaseen (Pharmacognosy Reviews)
Since ancient times, plants have been an exemplary source of medicine. Ayurveda and other Indian literature mention the use of plants in treatment of various human ailments. India has about 45,000 plant species and among them, several thousands have been claimed to possess medicinal properties. There are many plants which are having immunostimulatory whereas other have immunosuppressant activity. The present paper review plants which have shown experimental and clinincal immunomodulatory activity.
Keywords: Herbal plants; immunomodulation; phytochemistry; pharmacology